RARE-11. 60 years single centre experience of craniopharyngioma management. (3rd June 2022) - Rodrigues, Beryl; Adamski, Jenny; English, Martin; Curry, Helen; Solanki, Guirish; Peet, Andrew; Apps, John
Abstract: Adamantinomatous craniopharyngiomas are challenging intracranial tumours associated with significant morbidity. Management includes surgery and radiotherapy, with a shift towards more conservative surgery in recent years, aimed at preserving hypothalamic function. The West Midlands Regional Children's Tumour Registry collects detailed clinical, pathological and follow up information on patients treated within the region from 1957. 52 cases (26 male, 26 female) of craniopharyngioma treated at Birmingham Children's Hospital 1957-2018, were identified, with further clinical details obtained from patient records, where available. Visual symptoms were the commonest presenting feature (63%), followed by headache (48%), vomiting (31%), neurological symptoms (31%) and features of endocrine disorders (21%) with a median symptom duration of 6 months (range <1-24). Initial management was with gross total resection (GTR) in 14 patients, subtotal resection in 22 patients and subtotal resection with adjuvant radiotherapy in seven patients. Two patients received radiotherapy without resection, and five patients underwent cystic drainage procedures alone. Two patients initially underwent shunt insertion alone, but received radiotherapy at progression. 30 (58%) patients underwent relapse/progression, with a median time to progression of 1.2 years (range 0.2-6.3). 15 had further surgery. Radiotherapy was used in 14/15 patients who had not previously received radiotherapy, with the other undergoing a GTR. To date 10 patients have died, nine from tumour related reasons and one from pulmonary embolism. Where data was available at follow up, all patients had at least one endocrinopathy, with 38/45 patients having diabetes insipidus. Hypothalamic obesity was identified in 14/36 (39%) patients with sufficient records, with this more common in those undergoing GTR (7/9 (78%)) compared to other surgical procedures (7/27)(26%)(p<0.05). Three patients have developed neurovascular complications and three fatty liver disease. This experience is consistent with the literature and supports the increasing usage of hypothalamic sparing surgical management.